Promotion of Para-Chlorophenol Reduction and Extracellular Electron Transfer in an Anaerobic System at the Presence of Iron-Oxides - Jiang, Xinbai; Chen, Yuzhe; Hou, Chen; Liu, Xiaodong; Ou, Changjin; Han, Weiqing; Sun, Xiuyun; Li, Jiansheng; Wang, Lianjun; Shen, Jinyou (Frontiers in Microbiology, 2018)
Anaerobic dechlorination of chlorophenols (CPs) often subjects to their toxicity and recalcitrance, presenting low loading rate and poor degradation efficiency. In this study, in order to accelerate p-chlorophenol (p-CP) reduction and extracellular electron transfer in an anaerobic system, three iron-oxide nanoparticles, namely hematite, magnetite and ferrihydrite, were coupled into an anaerobic system, with the performance and underlying role of iron-oxide nanoparticles elucidated. The reductive dechlorination of p-CP was notably improved in the anaerobic systems coupled by hematite and magnetite, although ferrihydrite did not plays a positive role. Enhanced dechlorination of p-CP in hematite or magnetite coupled anaerobic system was linked to the obvious accumulation of acetate, lower oxidation–reduction potential (ORP) and pH, which were beneficial for reductive dechlorination. Electron transfer could be enhanced by Fe2+/Fe3+ redox couple on the iron oxides surface formed through dissimilatory iron-reduction. This study demonstrated that the coupling of iron-oxide nanoparticles such as hematite and magnetite could be a promising alternative to the conventional anaerobic reduction process for the removal of CPs from wastewater.